68Ga-DOTA chelate, a novel imaging agent for assessment of myocardial perfusion and infarction detection in a rodent model - Anu Autio; Sauli Uotila; Max Kiugel; Ville Kytö; Heidi Liljenbäck; Nobuyuki Kudomi; Vesa Oikonen; Olli Metsälä; Semi Helin; Juhani Knuuti; Antti Saraste; Anne Roivainen (Springer New York LLC, 2022)
Background
Magnetic resonance imaging (MRI) with Gadolinium 1,4,7,10-tetraazacyclododecane-N′,N″,N′′′,N″″-tetraacetic acid (Gd-DOTA) enables assessment of myocardial perfusion during first-pass of the contrast agent, while increased retention can signify areas of myocardial infarction (MI). We studied whether Gallium-68-labeled analog, 68Ga-DOTA, can be used to assess myocardial perfusion on positron emission tomography/computed tomography (PET/CT) in rats, comparing it with 11C-acetate.
Methods
Rats were studied with 11C-acetate and 68Ga-DOTA at 24 hours after permanent ligation of the left coronary artery or sham operation. One-tissue compartmental models were used to estimate myocardial perfusion in normal and infarcted myocardium. After the PET scan, hearts were sectioned for autoradiographic detection of 68Ga-DOTA distribution.
Results
11C-acetate PET showed perfusion defects and histology showed myocardial necrosis in all animals after coronary ligation. Kinetic modeling of 68Ga-DOTA showed significantly higher k1 values in normal myocardium than in infarcted areas. There was a significant correlation (r = 0.82, P = 0.001) between k1 values obtained with 68Ga-DOTA and 11C-acetate. After 10 minutes of tracer distribution, the 68Ga-DOTA concentration was significantly higher in the infarcted than normal myocardium on PET imaging and autoradiography.
Conclusions
Our results indicate that acute MI can be detected as reduced perfusion, as well as increased late retention of 68Ga-DOTA.